The presentation of authorship in medieval German narrative literature 1220-1290 - Coxon, Sebastian (Oxford modern languages and literature monographs., 2001)
This work sheds light on the complexity of medieval German literary culture as it evolved in the course of the thirteenth century (c.1220-1290) by analysing the attitudes of narrative poets towards the issue of authorship.